Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Comparative Outcomes of Combined Balloon Angioplasty and Intra-arterial Calcium Channel Blockers Versus Monotherapy for Cerebral Vasospasm Management: A Systematic Review and Meta-analysis - Basel Musmar; Atakan Orscelik; Joanna M. Roy; Stephanie Hage; Nimer Adeeb; Stavropoula I. Tjoumakaris; Michael Reid Gooch; Christina Notarianni; Bharat Guthikonda; Jacques Morcos; Robert H. Rosenwasser; Pascal Jabbour (Translational Stroke Research, 2025)

Cost-Effectiveness of Carotid Endarterectomy vs. Carotid Stenting: a Systematic Review and Meta-Analysis - Yash Akkara; Joshua J. Hon; Mahathir Ahmed; Basel Musmar; Joanna Roy; Stavropoula Tjoumakaris; Michael Reid Gooch; Robert H. Rosenwasser; Pascal Jabbour (Translational Stroke Research, 2025)
Introduction Carotid artery stenting (CAS) and carotid endarterectomy (CEA) are gold-standard treatments of carotid artery stenosis. This study aims to identify the cost-effectiveness of CEA vs CAS. Methods Studies were screened through PubMed, MEDLINE, and Embase using PRISMA guidelines, and required ≥ 20 participants who were ≥ 16 years, alongside costs at 1-year postoperatively. The Shapiro–Wilk test, independent sample t-tests, ANOVA, and Spearman’s R were used, with costs adjusted to 2024. A random-effects model was used to compare cost-effectiveness. Bias assessment was according to the Cochrane Risk of Bias 2.0 tool and the Newcastle–Ottawa Scale. Results 7 studies were included, with a sample of 6493 participants (3418 M, 3075 F). 2932 and 3511 participants underwent CEA and CAS respectively. CEA reported a significantly longer mean length of procedure (191.92 vs. 77.5 min, p < 0.0001) and length of stay (3.13 vs. 2.60 days, p < 0.0001) vs. CAS. The mean adjusted cost of CEA and CAS were $18156.60 (6466) and $17711.01 (5511) respectively. Studies reported lower risks of stroke (2.12% vs. 3.65%, p < 0.001), higher risks of myocardial infarctions (1.70% vs. 1.42%, p < 0.01), and higher risks of other complications for CEA vs. CAS respectively. The expected 1-year cost of CEA was marginally lower than CAS ($21264.03 vs. $21433.14, p < 0.05). The cost-effectiveness of CEA was marginally better than CAS (ratio = 1.019, 95% CI [1.017, 1.020)]. Conclusions CEA provides marginally improved cost-effectiveness over CAS, providing long-term cost benefits to centers with large surgical volumes. However, shorter procedural times and inpatient stays with CAS may improve overall productivity. Cost should hence not be a deciding factor when choosing between CEA and CAS.

Long-Term Outcomes of Stereotactic Radiosurgery Focused Treatment of Brain Arteriovenous Malformations Based on Rupture Status: A Systematic Review and Meta-Analysis - Meah T. Ahmed; Anand Kaul; Joanna Roy; Basel Musmar; Santiago D. Mendoza-Ayús; Morena P. Koorie; Cheritesh R. Amaravadi; Antony A. Fuleihan; Stavropoula I. Tjoumakaris; Michael R. Gooch; Robert H. Rosenwasser; Pascal Jabbour (Translational Stroke Research, 2025)

The Impact of Postprocedural Anticoagulant Use in Patients Undergoing Woven EndoBridge: A Multicenter Propensity Score-Matched Study - Basel Musmar; Hamza Adel Salim; Joanna M. Roy; Nimer Adeeb; Antony A. Fuleihan; Elias Atallah; Saman Sizdahkhani; Sravanthi Koduri; Spyridon Karadimas; Bachar El Baba; Brian M. Howard; Jonathan A. Grossberg; et al. (Translational Stroke Research, 2025)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Digital subtraction angiography in cerebrovascular disease: current practice and perspectives on diagnosis, acute treatment and prognosis - Shirin Shaban; Bella Huasen; Abilash Haridas; Murray Killingsworth; John Worthington; Pascal Jabbour; Sonu Menachem Maimonides Bhaskar (Acta Neurologica Belgica, 2022)

Endovascular Management of Cerebral Aneurysm - Mario Zanaty; Nohra Chalouhi; Stavropoula I. Tjoumakaris; Robert H. Rosenwasser; Pascal M. Jabbour (Translational Stroke Research, 2014)

Molecular Imaging of Cerebrovascular Lesions - Nohra Chalouhi; Pascal Jabbour; Vincent Magnotta; David Hasan (Translational Stroke Research, 2014)